Efficacy of Central Neck Dissection for Clinically Node-Negative Papillary Thyroid Carcinoma: Propensity Scoring Matching - Yoo, Byung Joon; Song, Chang Myeon; Ji, Yong Bae; Lee, Ji Young; Park, Hae Jin; Tae, Kyung (Frontiers in Endocrinology, 2019)
Objectives: The utility of prophylactic central neck dissection (pCND) for papillary thyroid carcinoma (PTC) is still controversial. Although the procedure may reduce locoregional recurrence, it is associated with a high rate of postoperative complications. The aim of this study was to evaluate the role of pCND in patients with PTC. Materials and Methods: From January 1995 to April 2011, the records of 477 patients who underwent total thyroidectomy with or without pCND for clinically node-negative PTC measuring < 4 cm were retrospectively reviewed. Of these, 341 patients had undergone pCND with total thyroidectomy and 136 patients did not undergo pCND. The clinicopathologic characteristics, surgical outcomes, complications, recurrence, and survival were analyzed using propensity score matching, using age, sex, tumor size, extrathyroidal extension, and radioactive iodine ablation as covariates to minimize selection bias. Results: At baseline, there was no significant difference in sex, age, and multiplicity and bilaterality of the cancer between the two groups. However, extrathyroidal extension was more common and tumor size larger in patients who underwent pCND. For the propensity score-matched analysis, two matched groups, each comprising 135 patients, were generated. After propensity score matching, the significant differences observed at baseline between the two groups disappeared. The postoperative complication rate did not differ between the two groups. Recurrence occurred in 4 patients (2.96%) who had undergone pCND and in 2 patients (1.48%) who did not undergo pCND (P = 0.684). The recurrence-free survival curves did not differ between the two groups. Conclusion: The efficacy of pCND in total thyroidectomy for clinically node-negative PTC is limited, and pCND is not recommended for these patients.